Homozygous FIBP nonsense variant responsible of syndromic overgrowth, with overgrowth, macrocephaly, retinal coloboma and learning disabilities. Issue 5 (20th January 2016) - Thauvin‐Robinet, C.; Duplomb‐Jego, L.; Limoge, F.; Picot, D.; Masurel, A.; Terriat, B.; Champilou, C.; Minot, D.; St‐Onge, J.; Kuentz, P.; Duffourd, Y.; Thevenon, J.; et al.
Abstract : The acidic fibroblast growth factor (FGF) intracellular binding protein (FIBP) interacts directly with the fibroblast growth factor FGF1. Although FIBP is known to be implicated in the FGF signaling pathway, its precise function remains unclear. Gain‐of‐function variants in several FGF receptors (FGFRs) are implicated in a wide spectrum of growth disorders from achondroplasia to overgrowth syndromes. In a unique case from a consanguineous union presenting with overgrowth, macrocephaly, retinal coloboma, large thumbs, severe varicose veins and learning disabilities, exome sequencing identified a homozygous nonsense FIBP variant. The patient's fibroblasts exhibit FIBP cDNA degradation and an increased proliferation capacity compared with controls. The phenotype defines a new multiple congenital abnormalities (MCA) syndrome, overlapping with the heterogeneous group of overgrowth syndromes with macrocephaly. The different clinical features can be explained by the alteration of the FGFR pathway. Taken together, these results suggest the implication of FIBP in a new autosomal recessive MCA.